Air Pollution Trend Analysis in Hangzhou during the Asian Games - Anbu Clemensis Johnson (International Journal of Scientific Research in Science and Technology, 2026)
This study examines the temporal dynamics of air pollution in Hangzhou, China, during 2023, with a particular focus on the Asian Games period (September-October 2023). Monthly average concentrations of six criteria pollutants (PM2.5, PM10, NO2, O3, SO2, and CO), together with four meteorological parameters, were used to evaluate the effectiveness of short-term regulatory interventions implemented for the mega-event. The results indicate substantial reductions in primary pollutants during the Games, especially NO2 (19 μg/m³ in September compared with an annual average of 30.1 μg/m³) and PM10 (40.5 μg/m³ during the Games versus 53.4 μg/m³ prior to the event), reflecting the effectiveness of traffic and industrial control measures. In contrast, ozone concentrations remained elevated (125.2 μg/m³), likely driven by favourable photochemical conditions, highlighting the challenges associated with managing secondary pollutants. A pronounced rebound effect was observed in November-December, with PM2.5 and NO2 increasing by 69.2 % and 76.5 %, respectively, relative to Games-period levels. Overall, the findings demonstrate that while temporary emission controls can deliver short-term air quality improvements, sustainable urban air quality management requires integrated, long-term strategies, and the study provides policy-relevant insights for future mega-events in rapidly developing urban environments.
Keywords: Air quality management; Mega-events; Asian Games; Hangzhou; Pollution rebound effect; Environmental policy